Civic Engagement and Social Responsibility Among SHS Teachers in the City of Santa Rosa: Basis for Civic Consciousness Program - Rosalie Delmo De Vera; Alex S. Sanchez (Researchparks Publishing, 2026)
This study investigated the level of civic engagement and social responsibility among public Senior High School (SHS) teachers in Santa Rosa City during the Academic Year 2025–2026 as a basis for the development of a proposed Civic Consciousness Program. Specifically, the study examined the demographic profile of respondents in terms of age, sex, civil status, teaching experience, and assigned SHS strands or tracks. It further assessed the level of civic engagement in relation to active participation in governance and community life, as well as the level of social responsibility concerning ethical duties and accountability to society. A quantitative descriptive-correlational research design was employed, utilizing a researcher-made questionnaire administered to 207 public SHS teachers selected through stratified random sampling from a population of 241 teachers across ten public secondary schools in Santa Rosa City. Data were analyzed using frequency and percentage distribution, weighted mean, t-test, one-way analysis of variance (ANOVA), post hoc analysis, and Pearson Product-Moment Correlation Coefficient. Findings revealed that public SHS teachers demonstrated high levels of civic engagement and social responsibility, indicating strong participation in civic-related activities and commitment to ethical accountability. Significant differences were observed when grouped according to selected demographic variables, while a statistically significant positive relationship existed between civic engagement and social responsibility. The study concluded that teachers serve as vital agents of civic consciousness and social transformation. Consequently, the findings served as the basis for a proposed Civic Consciousness Program aimed at strengthening teachers’ participation in civic and socially responsible initiatives.